Social Return on Investment of Curriculum and Learning Packages in Innovative Agriculture Suitable for the Local Context to Promote Food Security and Grassroots Economy Development - Deenang, Exkarach; Boonmee, Sawitree; Paisan, Teeraporn (Journal of Human and Society, Sisaket Rajabhat University, 2025)
The purpose of this research was to assess the social return on investment (SROI) of curriculum and learning packages in innovative agriculture tailored to the local context, with the goal of promoting food security and grassroots economic development. A mixed-method research approach with a convergent parallel design was employed. Qualitative data were collected from 15 key informants through focus group discussions using a semi-structured interview guide based on the three-pillar framework (economic, social, and environmental dimensions), and were analyzed using a social impact pathway to summarize the impacts. Quantitative data were obtained from 160 respondents through structured questionnaires and analyzed using descriptive statistics. The SROI was then calculated. The results revealed that the curriculum significantly enhanced the potential of learners and local stakeholders, enabling them to contribute to food security and precision agriculture in ways that support sustainable community economies. Specifically, 97.50% stated it met local needs, 95.63% of participants perceived benefits from the curriculum, and 88.13% reported applying the acquired knowledge in practice. The average SROI value was found to be 2.82, meaning that every 1 THB invested in the curriculum yielded 2.82 THB in social value. These findings demonstrate the cost-effectiveness and social value of the curriculum and learning packages developed by the university for community development.